2008
DOI: 10.1093/nar/gkn091
|View full text |Cite
|
Sign up to set email alerts
|

The small RNA GlmY acts upstream of the sRNA GlmZ in the activation of glmS expression and is subject to regulation by polyadenylation in Escherichia coli

Abstract: In Escherichia coli the glmS gene encoding glucosamine 6-phosphate (GlcN-6-P) synthase GlmS is feedback regulated by GlcN-6-P in a pathway that involves the small RNA GlmZ. Expression of glmS is activated by the unprocessed form of GlmZ, which accumulates when the intracellular GlcN-6-P concentration decreases. GlmZ stabilizes a glmS transcript that derives from processing. Overexpression of a second sRNA, GlmY, also activates glmS expression in an unknown way. Furthermore, mutations in two genes, yhbJ and pcn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
179
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(202 citation statements)
references
References 35 publications
18
179
1
4
Order By: Relevance
“…The shorter GlmY* (z140 nt) is an exception, being the predominant RNA detected in the wild type. This has been previously observed as the full-length GlmY (z180 nt) is rapidly processed in the 39-end to originate the GlmY* species (Reichenbach et al 2008;Urban and Vogel 2008). Overexpression of PNPase in the hfq pnp strain was shown to reverse the accumulation of MicA* (Supplemental Fig.…”
Section: Inactivation Of Pnpase Markedly Increases the Levels Of Smalsupporting
confidence: 59%
See 1 more Smart Citation
“…The shorter GlmY* (z140 nt) is an exception, being the predominant RNA detected in the wild type. This has been previously observed as the full-length GlmY (z180 nt) is rapidly processed in the 39-end to originate the GlmY* species (Reichenbach et al 2008;Urban and Vogel 2008). Overexpression of PNPase in the hfq pnp strain was shown to reverse the accumulation of MicA* (Supplemental Fig.…”
Section: Inactivation Of Pnpase Markedly Increases the Levels Of Smalsupporting
confidence: 59%
“…This was also confirmed to be a consequence of the higher stabilization of GlmY* in the hfq pcnB mutant (data not shown). GlmY* is known to be highly polyadenylated in cells harboring Hfq (Reichenbach et al 2008;Urban and Vogel 2008). We have now shown that the lack of poly(A) polymerase I is an important factor affecting the sRNA decay in the absence of Hfq in stationary-phase cells.…”
Section: Inactivation Of Pnpase Markedly Increases the Levels Of Smalmentioning
confidence: 81%
“…The half-life of OxyS in E. coli K12 wild type was reported to be 12-15 min, 14 the half-life in strain MC4100 can create new RNase cleavage sites 18,26 or protect from cleavage. 27,28 While RNase III preferentially cleaves double stranded RNA regions, RNase E recognizes single stranded AU rich segments. 29 To address the role of these RNases in OxyS decay we analyzed RNase deficient strains and compared OxyS stability in the isogenic wild type backgrounds.…”
Section: Resultsmentioning
confidence: 99%
“…Regulation of ncRNAs by polyadenylation was well characterized in the glmS/glmZ/glmY system (Kalamorz et al, 2007;Reichenbach et al, 2008). Translation of the glmS mRNA was normally weak since an internal hairpin structure containing the glmS Shine Dalgarno sequence limits ribosome access to the downstream glmS RBS and therefore GlmS synthesis (Kalamorz et al, 2007;Urban et al, 2008).…”
Section: Non-templated Additions On the 3'ends Of Ncrnamentioning
confidence: 99%
“…for gadY, , dsrA , and glmY (Reichenbach et al, 2008)) and is believed to involve post-transcriptional processing that is dependent on the balance between protection by RNA binding protein(s) and degradation by RNases. The functional significance has not been well-studied but, importantly, Davis and Waldor (Davis and Waldor, 2007) have shown that MicX of Vibrio cholerae can be detected as both an active precursor and a processed form and that the smaller, processed molecule is significantly more stable and abundant.…”
Section: Significance Of Multible Bands For a Single Ncrnamentioning
confidence: 99%